Cyclopedia of Commerce, Accountancy, Business Administration, v. 03 (of 10) - American School of Correspondence (Salt Lake City, UT : Project Gutenberg, 2014)
"Cyclopedia of Commerce, Accountancy, Business Administration, v. 03 (of 10)" is a comprehensive reference work published in the early 20th century. This volume focuses on various aspects of commercial law, contracts, and agency, making it a valuable resource for those in the fields of business, finance, and law. The book is compiled by a team of experts, including accountants and attorneys, to provide up-to-date and practical guidance on business practices and legal principles. The opening of this volume introduces the rationale behind its compilation, noting an increase in commercial activities that necessitate better business methods. With the proliferation of information on business practices being scattered throughout various sources, the foreword emphasizes the intention to create a centralized resource that encapsulates the best practices across different branches of business. The text outlines significant topics, including the law of contracts, sales, property, and agency, setting the stage for detailed discussions that follow which are intended to serve students, practitioners, and those interested in mastering modern business methods. (This is an automatically generated summary.)
Release date is 2014-08-03
Giovanni Fini, Juliet Sutherland and the Online Distributed Proofreading Team
Keywords: Business; Commerce; Accounting